Extending resonant inelastic X-ray scattering to the extreme ultraviolet - Wray, L. Andrew; Huang, Shih-Wen; Jarrige, Ignace; Ikeuchi, Kazuhiko; Ishii, Kenji; Li, Jia; Qiu, Z. Q.; Hussain, Zahid; Chuang, Yi-De (Frontiers in Physics, 2015)
In resonant inelastic X-ray scattering (RIXS), core hole resonance modes are used to enhance coupling between photons and low energy electronic degrees of freedom. Resonating with shallow core holes accessed in the extreme ultraviolet (EUV) can provide greatly improved energy resolution at standard resolving power, but has been found to often yield qualitatively different spectra than similar measurements performed with higher energy X-rays. This paper uses experimental data and multiplet-based numerical simulations for the M-edges of Co-, Ni- and Cu-based Mott insulators to review the properties that distinguish EUV RIXS from more commonly performed higher energy measurements. Key factors such as the origin of the strong EUV elastic line and advantages of EUV spectral functions over soft X-ray RIXS for identifying intrinsic excitation line shapes are discussed.